Results of a Human Papillomavirus Self-Collection Educational Intervention for Health Care Providers in Appalachia - Mira L. Katz; Abigail Shoben; Amie M. Ashcraft; Emma Mitchell; Mark Dignan; Sarah Cooper; Mark Cromo; Jean Walunis; Deborah Flinner; Dannell Boatman; Lindsay Hauser; Mack T. Ruffin; et al. (Women's Health Reports)
Objective: There is an increasing interest in human papillomavirus (HPV) self-collection as a strategy for women not up-to-date with cervical cancer screening. We report the findings of an HPV self-collection educational intervention for health care providers and staff. Materials and Methods: As part of the Health Outcomes through Motivation and Education (HOME) Initiative, health care providers from 10 health care systems in Appalachian regions of four states attended online sessions during 2021–2023. Participants (n = 167) completed pre- and postintervention surveys focused on knowledge and attitudes about HPV self-collection and cervical cancer screening. The postintervention survey also addressed satisfaction with the educational intervention. Results: Participants correctly answered an average of 4.6 out of 7 knowledge items on preintervention surveys and an average of 6.0 items on postintervention surveys (p < 0.001). Attitudes were more positive on postintervention surveys and included that participants reported that they were better informed about HPV self-collection and more confident they could talk to patients about HPV self-collection (both p < 0.05). Nearly all (>97%) participants reported being satisfied with the educational intervention and being pleased their health center was included in the HOME Initiative. Conclusions: An online educational intervention for health care providers and staff about HPV self-collection as a cervical cancer screening strategy was efficacious in improving knowledge and attitudes and was well-received by participants. Given its online delivery and that it can be completed individually or in a group setting, this educational intervention with minor adaptations has potential for wide dissemination to educate health care providers and staff about HPV self-collection.